Comprehensive quality of discharge summaries at an academic medical center. Issue 8 (22nd March 2013) - Horwitz, Leora I.; Jenq, Grace Y.; Brewster, Ursula C.; Chen, Christine; Kanade, Sandhya; Van Ness, Peter H.; Araujo, Katy L. B.; Ziaeian, Boback; Moriarty, John P.; Fogerty, Robert L.; Krumholz, Harlan M.
Abstract : BACKGROUND: Discharge summaries are essential for safe transitions from hospital to home. OBJECTIVE: To conduct a comprehensive quality assessment of discharge summaries. DESIGN: Prospective cohort study. SUBJECTS: Three hundred seventy‐seven patients discharged home after hospitalization for acute coronary syndrome, heart failure, or pneumonia. MEASURES: Discharge summaries were assessed for timeliness of dictation, transmission of the summary to appropriate outpatient clinicians, and presence of key content including elements required by The Joint Commission and elements endorsed by 6 medical societies in the Transitions of Care Consensus Conference (TOCCC). RESULTS: A total of 376 of 377 patients had completed discharge summaries. A total of 174 (46.3%) summaries were dictated on the day of discharge; 93 (24.7%) were completed more than a week after discharge. A total of 144 (38.3%) discharge summaries were not sent to any outpatient physician. On average, summaries included 5.6 of 6 The Joint Commission elements and 4.0 of 7 TOCCC elements. Summaries dictated by hospitalists were more likely to be timely and to include key content than summaries dictated by housestaff or advanced practice nurses. Summaries dictated on the day of discharge were more likely to be sent to outside physicians and to include key content. No summary met all 3 quality criteria of timeliness, transmission, and content. CONCLUSIONS: Discharge summary quality is inadequate in many domains. This may explain why individual aspects of summary quality such as timeliness or content have not been associated with improved patient outcomes. However, improving discharge summary timeliness may also improve content and transmission. Journal of Hospital Medicine 2013;8:436–443. © 2013 Society of Hospital Medicine